1997
DOI: 10.1177/107110079701800610
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondritis Dissecans of the Head of the Talus

Abstract: We present a case of osteochondritis dissecans of the head of the talus, without a history of trauma. The clinical and radiological features and a 2-year and 3-month follow-up are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…However, talar osteochondral lesions can occur without a history of trauma, 8,10,12,15,17 and several theories as to their etiology have been proposed including repeated microtrauma, ossification abnormalities, endocrine factors, abnormal vasculature, embolic phenomena, and genetic predisposition. 7,10,19 MRI has become a valuable tool in the diagnosis and staging of talar osteochondral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, talar osteochondral lesions can occur without a history of trauma, 8,10,12,15,17 and several theories as to their etiology have been proposed including repeated microtrauma, ossification abnormalities, endocrine factors, abnormal vasculature, embolic phenomena, and genetic predisposition. 7,10,19 MRI has become a valuable tool in the diagnosis and staging of talar osteochondral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…One of our patients had a much longer follow-up (7 years) than the previously reported two patients, who had a follow-up of 12 and 27 months, respectively [5,6]. Their symptoms resolved with rest, judicious use of antiinflammatory medications, and activity modification.…”
Section: Discussionmentioning
confidence: 53%
“…Osteochondritis involving the talar head has been mentioned in only two previously published reports in English literature [5,6]. These are both case reports with a short follow-up (12 and 27 months, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…The condition was first described by Sir James Paget in 1870 and the term osteochondritis dissecans was coined by Kö nig some 7 years ( Dickson & Sartoris, 1991;Dipaola et al, 1991;Canosa, 1994;Woods & Harris, 1995;Dolan et al, 1997;Iannacone & Dalton, 1997;Higuera et al, 1998). Other ankle locations, including the calcaneus (Nafei et al, 1990), the navicular (Richter et al, 1985;Walther-Larsen & Larsen, 1985;Exner et al, 1991) and the cuboid (Anderson, 2000) are extremely rare.…”
Section: Discussionmentioning
confidence: 94%
“…Formerly, it was considered to be secondary to trauma but more recent research has shown that not all cases are associated with injury (Mubarak & Carroll, 1981;Dolan et al, 1997). It is possible that a localized delay in ossification may be responsible for the defect (Barrie, 1987).…”
Section: Discussionmentioning
confidence: 98%